Types of Forestry Charges from Natural Resource Economics Perspective - Sudarsono Soedomo (Institut Pertanian Bogor (IPB University), 2012)
Capturing economic rent from natural resources, particularly forests, frequently still creates disagreement between the government and businesses. The charges imposed by the government in the forms of reboisation fund (DR) and forest resource provision (PSDH) have been in place for very long time, accepted by all stakeholders, and supported by laws. Government policy regarding compensation for forest stand value (GRNT) creates controvercies. This paper intends to clarify problem of forest charges by returning it to its fundamental theories, e.g. economic theory of natural resouces. Economic rent of forests that are controlled by the government is the right of all Indonesia people. Henece, the government has responsibility for capturing the rent as much as possible in the most efficient way. If the stumpage is too low then it potentially promotes overcutting, whereas if it is too high then it makes forest business less attractive that potentially promotes illegal activities. In forestry, economic rent of forest has a special name, it is stumpage price. There are some difficulties in estimating a competitive stumpage price, wheter the one obtained through a direct competitive auction of standing timber or through calculation of residual price. Partly, the difficulties were generated by the government’s own policies that strongly distorted log prices. Log export ban and vertical integration are the two most influential policies in distorting log prices. Actually, the government is able to design and implement a single charge to capture PSDH, DR, and GRNT so that their administration becomes much simpler and more efficient.